Neurodevelopmental milestones and associated behaviours are similar among healthy children across diverse geographical locations - José Villar (Nature Portfolio, 2019)
It is unclear whether the sequence and timing of early life neurodevelopment varies across human populations, excluding the effects of disease or malnutrition. Here, the authors show that children of healthy, urban, educated mothers show very similar development across five geographically diverse populations.